Analysis of sociodemographic factors as a trigger for a passive lifestyle of the college student in Malang - Dian Pitaloka Priasmoro (Babali Nursing Research, 2023)
Introduction: Passive lifestyles carried out by community groups, such as among students, can cause health problems in the future, such as the emergence of degenerative diseases and endocrine diseases. Certain lifestyles that are carried out can be influenced by internal factors such as sociodemographic factors. This study aims to analyze the sociodemographic factors that trigger passive lifestyle behaviour in students. Methods: the design of this research is a description. The research was conducted in June 2022, involving 127 respondents from Malang city. The population in this study were students in the town of Malang; the research sample was some students who lived passive lifestyles. The sampling technique used purposive sampling with the criteria that students were living a passive lifestyle, as evidenced by a score of less than 36 (inactive lifestyle) obtained from screening using a questionnaire. The International Physical Activity Questionnaire (IPAQ) is used to identify the passive.Furthermore, the data were analyzed by bivariate analysis with chi-square and multivariate with odds ratio. Results: the results of the study show that the education factor triggers a passive lifestyle among students, with a value of 13.625 or 13.6%, meaning that 13.6% of the trigger for an inactive lifestyle is from the education factor. Conclusion: based on the study's results, it can be concluded that a person's behaviour is determined mainly by their attitudes and understanding. So it is essential to give massive educational efforts to teenagers about the impact of a passive lifestyle to change their behaviour.